Integrative Sex Education For Children - Maya Fitria (UIN Sunan Kalijaga, 2017)
This study aims to describe how parents conduct early sexual education for their children. The outlines for early sexual education include reproductive health and sexuality issues in biological, medical, religious, social, cultural, and psychological explanations. Informants consist of parents who are educated max high school and parents who are highly educated (S2) and work as teachers and lecturers (15 people). The research data was explored using literature method, interview, and Focus Group Discussion (FGD). The results showed that parents who are both highly educated and low have difficulty in conducting sexual education in their children. However, highly educated parents seem more able to overcome barriers in providing early sexual education. Good knowledges on reproductive health and sexuality make them able to express advice and guidance on reproduction and sexuality matters. However, parents still need to know more about the sexual education materials which given in schools so that there will be consistency between parents and teachers. Forms of early sexual education at home are explainations, prohibitions, discussions, suggestions, examples or modeling, and brief conversations. The compactness of father and mother and school along with the consistency of the way and the material is very helpful to achieve the goal of early sexual education. Integrative early sex education is agreed upon by the respondent and the result of a researcher's textual study as a sexual education that leads to abstinence by considering how religious texts speak about the content, and methods of delivery. Sciences related to early sex education are: psychology, religion, biology, medical, sociology, gender analysis, information technology, economics, law, and so on.